Pengaruh Stress Akademik terhadap Emotional Eating pada Mahasiswa Psikologi Universitas Negeri Padang - Prasetya, Genta; Hidayati, Izzanil (Lembaga Yasin AlSys, 2024)
The study was conducted to analyze the influence of academic stress on emotional eating behavior among Psychology students at Universitas Negeri Padang. The background of this research highlights the high academic demands that can trigger stress and lead to emotional eating patterns as an unhealthy coping mechanism. The method employed in this study is a quantitative approach with descriptive analysis and Pearson correlation tests. The research sample consists of 60 fifth-semester psychology students selected using purposive sampling techniques. Data were collected through an online questionnaire distributed using a Likert scale.The results of the study indicate a significant but weak positive relationship between academic stress and emotional eating behavior, with a correlation value of 0.357 and p < 0.05. The conclusion drawn from this research is that high levels of academic stress can trigger emotional eating behavior, although the correlation is relatively weak (Ha is accepted). Therefore, effective interventions are needed to manage academic stress to prevent its negative impacts on students' physical and mental health.